The dream weavers : strategy-focused leadership in technology-driven organizations - Sosik, John J.; Jung, Don I.; Berson, Yair; Dionne, Shelley D.; Jaussi, Kimberly S. (Emerald Publishing Limited : Information Age Publishing, 2004)
The main question that guided the thinking behind this book can be stated as follows: "What kind of leadership behavior must executives of technology-driven organizations display to spur performance excellence?" To address this question the authors conducted videotaped interviews of executives from 65 organizations- including General Electric, Qualcomm, The Vanguard Group, and Barclays Global Investors - to identify common behaviors and traits that lead to organizational success. In addition to the interviews, they surveyed the executives' followers to evaluate the leadership and organizational culture to examine successful executive leadership from multiple reference points. The authors found that displaying outstanding executive leadership doesn't necessarily require a commanding presence, a genius-level IQ, expertise, or even a strong command and control system. At the heart of outstanding strategic leadership was an ability to envision a strategy for taking the raw inputs provided by their environments (e.g., people, technology, ideas, opportunities) and then to weave them into an integrated pattern or system of social, technical and intellectual resources that ultimately produce dramatically higher levels of organizational success factors. The book includes dozens of stories and narratives from the executive leaders to offer readers an in-depth look at what constitutes effective strategy-focused leadership in technology-driven organizations.
Keywords: Leadership.; Strategic planning.; Industrial management.; Technological innovations.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books